2001
DOI: 10.1111/j.1447-0756.2001.tb01273.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Intraplacental Villous Arteries by Latex Cast Model in vitro and Color Doppler Flow Imaging in vivo*

Abstract: Color Doppler flow sonography is a valuable tool for detecting the blood flow of intraplacental villous arteries in vivo and the images agree with the vascular anatomy of placenta in vitro. These results may also provide the basic parameters for future studies of some complicated pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…It is well accepted that a normal mature placenta is composed of about 25 cotyledons. 11 Observation of our placental casts 20 also revealed that each cotyledon is supplied by 2-3 IP arteries that branch off the chorionic plate. Accordingly, we assumed that each umbilical artery may supply about 25 IP arteries, and thus, the outflow from each IP vessel is 4% of the total perfusion from each umbilical artery.…”
Section: Boundary Conditionsmentioning
confidence: 82%
See 1 more Smart Citation
“…It is well accepted that a normal mature placenta is composed of about 25 cotyledons. 11 Observation of our placental casts 20 also revealed that each cotyledon is supplied by 2-3 IP arteries that branch off the chorionic plate. Accordingly, we assumed that each umbilical artery may supply about 25 IP arteries, and thus, the outflow from each IP vessel is 4% of the total perfusion from each umbilical artery.…”
Section: Boundary Conditionsmentioning
confidence: 82%
“…The IP vessels give rise to the villous trees or about 27 cotyledons that are the essential structures involved in material exchange between mother and fetus. [8][9][10][11] Classification of branching networks in bioengineering and physiology was commonly done by using the definitions of dichotomous and monopodial patterns. [12][13][14][15][16][17][18][19] The dichotomous pattern defines a symmetric network that repeatedly branches into two fairly similar daughter vessels.…”
Section: Abstract: Placenta; Blood Perfusion; Dichotomous Bifurcationmentioning
confidence: 99%
“…To date, most experimental placental imaging techniques are being used in post mortem specimens and consist of vascular corrosion casting and microcomputed tomography [28–30]. These techniques investigate normal villous vasculogenesis and angiogenesis, by (i) applications of corrosion casts and observations under a scanning electron microscope, (ii) injection of contrast medium, or (iii) using a classical microscope and manual 3D reconstructions of paraffin sections.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques investigate normal villous vasculogenesis and angiogenesis, by (i) applications of corrosion casts and observations under a scanning electron microscope, (ii) injection of contrast medium, or (iii) using a classical microscope and manual 3D reconstructions of paraffin sections. Though these techniques have improved over the years, they still provide qualitative evaluation of placental phenotypes [18, 28–30]. The advantage of the proposed technique is its specificity to target placental neovascularization, a key aspect of placental development.…”
Section: Discussionmentioning
confidence: 99%
“…The hypo‐echoic space was intermingled with small, segmented, placental‐like tissues. Thorough examination using color Doppler flow imaging may be useful for detecting this abnormality of the villous trees 6 . Accordingly, when IUGR is accompanied by an unusual placenta with the above USG findings, cotyledonary‐like placenta with poor development of villous trees can be considered, and fetal well‐being should be monitored carefully.…”
Section: Discussionmentioning
confidence: 99%